STABLE COMPARATIVE CONSTRUCTIONS IN LITERARY DISCOURSE - Parvana Abbasova Zahid (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This paper examines stable comparative constructions as a distinct type of phraseological unit in literary texts. These constructions combine lexical fixation with semantic cohesion, allowing them to convey both denotative comparison and evaluative or emotional nuance. Their structural stability supports reproducibility, while contextual flexibility enables creative expression. Through analysis of Azerbaijani literary discourse, the study demonstrates how stable comparative units contribute to imagery formation, textual cohesion, and stylistic organization. The findings highlight the cognitive, semantic, and cultural dimensions of these constructions, underscoring their significance as both linguistic and aesthetic tools.